Polluting emissions emitted by public transport vehicles based on the Simplified Emissions Estimation Model, city of Chimbote - Peru - CHUCUYA HUALLPACHOQUE, ROBERTO CARLOS; Díaz Bernabé, Shanel Victoria; Villena Linares, Diego Hernando; LEON LEON, RYAN ABRAHAM (LACCEI, 2024)
The report presents a detailed study on the polluting emissions generated by the public transportation system in Chimbote, Peru. The methodology adopted included conducting interviews with drivers belonging to 12 public transportation lines, with the purpose of collecting detailed information about the vehicles, including aspects such as brand, model, year of manufacture and type of fuel. Subsequently, the simplified SEEM model was used in conjunction with the emission factors established by EURO standards to estimate emissions. The emissions analysis was carried out considering each transportation line individually, highlighting that line 8 emits 26,326 g/min and line 12, 20,734 g/min, being identified as the most polluting. Likewise, emissions were examined depending on the year of manufacture of the vehicles, revealing that those manufactured before the year 2000 emit 55,307 g/min additional pollutants due to their high emission factors. In conclusion, a greater contribution to air pollution by older vehicles is evident. In the comparison of emissions according to the type of fuel used, it was concluded that Liquefied Petroleum Gas (LPG) is significantly more polluting than gasoline, generating 155,261 g/min of additional emissions. This disparity is explained by the wide preference and use of LPG in the city of Chimbote, being a determining variable in the observed pollution levels.